2018
DOI: 10.1002/jcb.26883
|View full text |Cite
|
Sign up to set email alerts
|

The LncRNA H19/miR‐193a‐3p axis modifies the radio‐resistance and chemotherapeutic tolerance of hepatocellular carcinoma cells by targeting PSEN1

Abstract: This study was designated to verify if the lncRNA H19/miR-193a-3p axis would play a regulatory role in the radio-/chemo-resistances of HCC cells through targeting PSEN1. Within the study, five human HCC cell lines were prepared, including Bel-7402, HepG2, Hep3b, QGY-7703, and SMMC-7721. Moreover, docetaxel (DT), paclitaxel (Pt), vinorelbine (Vb), and 5-fluorouracil (5-Fu) were managed as the chemo-therapeutics, and single-dose X-rays were performed as radio-therapies. Besides, lncRNA H19 and miR-193a-3p were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…On one hand, Ham, S et al reported the inverse correlation of AD and cancer observed in the Presenilin1-KO mouse model of AD [20]. The downregulation of Presenilin1 in hepatocellular carcinoma cells promotes cell survival and decreases cell apoptosis to modify radioresistance and chemotherapeutic tolerance [14]. Similarly, the expression level of Presenilin1 is negatively correlated with bladder cancer chemoresistance [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, Ham, S et al reported the inverse correlation of AD and cancer observed in the Presenilin1-KO mouse model of AD [20]. The downregulation of Presenilin1 in hepatocellular carcinoma cells promotes cell survival and decreases cell apoptosis to modify radioresistance and chemotherapeutic tolerance [14]. Similarly, the expression level of Presenilin1 is negatively correlated with bladder cancer chemoresistance [12].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Presenilin1 regulates the paired phosphorylation of β-Catenin independently of Axin/CK-1α in tumorigenesis [9]. Presenilin1 was reported to be involved in ovarian cancer [10], gastric cancer [11], bladder cancer [12], colorectal cancer [13] and hepatocellular carcinoma [14]. However, despite AD being most frequent disease of neurology and glioblastoma being most common tumor of neurosurgery departments, the detailed roles of this AD-related molecule in glioblastoma have not yet been thoroughly validated, and the underlying mechanism needs to be clarified.…”
mentioning
confidence: 99%
“…24 Additionally, lncRNA H19 triggered the radioresistance of HCC cells by acting as a ceRNA for miR-193a-3p and upregulating PSEN1. 25 Furthermore, knockdown of lncRNA ROR sensitized HCC cells to radiation via regulating the microRNA-145/RAD18 axis. 26 Similar to previous studies, LINC00473 expression was prominently up-regulated in HCC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-193a-3p suppressed ovarian cancer cell growth and migratory/invasive capacities [28]. MiR-193a-3p had also been proven to be related to the migration and invasion [14], proliferation and apoptosis [15,16], radioresistance, and chemotherapeutic tolerance in HCC [29,30]. In addition, the expression of miR-193a-3p was identi ed as a predictor of HCC progression-free survival [31].…”
Section: Discussionmentioning
confidence: 99%